2016
DOI: 10.3390/laws5020017
|View full text |Cite
|
Sign up to set email alerts
|

Can International Human Rights Law Help Restore Access to Justice for Disabled Workers?

Abstract: The research literature indicates that legislative changes in recent years, including the introduction of tribunal fees, have made it harder for workers in general to enforce their rights under UK employment laws. Drawing on the author's qualitative study, conducted in 2015 and with information from 265 participants, this paper finds that these legislative changes could be having disproportionate adverse impacts on disabled workers. Of particular note, fees had deterred substantial numbers from submitting disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The author's qualitative Reasonable Adjustments Study (RAS) was undertaken between April and November 2015; and ran alongside his study of the enforcement of equality law, which is reported elsewhere in this journal [42]. The sources of data are shown below.…”
Section: Generalisationmentioning
confidence: 99%
See 4 more Smart Citations
“…The author's qualitative Reasonable Adjustments Study (RAS) was undertaken between April and November 2015; and ran alongside his study of the enforcement of equality law, which is reported elsewhere in this journal [42]. The sources of data are shown below.…”
Section: Generalisationmentioning
confidence: 99%
“…Identified relevant external (to the organisation) factors included the economic environment and social norms; and, the focus of the rest of this paper, the wording and interpretation of the Reasonable Adjustments Duty and other employment and equality laws, and government flexible labour force policies, which are taken to include employment and equality law deregulation and welfare reform. As enforcement of employment and equality law is the subject of a separate paper [42], it is not dealt with further below.…”
Section: The Impact Of Adjustments and The Reasonable Adjustments Dutymentioning
confidence: 99%
See 3 more Smart Citations